Analisis Hukum terhadap Tindak Pidana Pencemaran Nama Baik di Dunia Maya Berdasarkan UU ITE - Arif Budiman; Rayhan Oktaviandra (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Defamation in cyberspace has become a serious legal issue alongside the rapid development of information technology and social media. The widespread use of digital platforms allows information to be disseminated quickly, but also increases the potential for acts that harm a person’s honor and reputation. In Indonesia, defamation is regulated under the Criminal Code and specifically through the Law on Information and Electronic Transactions (ITE Law), which provides distinct legal mechanisms and sanctions for offenses committed via electronic media. A normative legal approach with descriptive-analytical methods is employed by examining statutory regulations, legal doctrines, and relevant legal literature to analyze the regulation and enforcement of defamation offenses in the digital sphere. The analysis shows that Article 27 paragraph (3) of the ITE Law serves as the main legal basis for addressing online defamation, with criminal sanctions regulated separately under Article 45. However, its implementation faces significant challenges, including differing interpretations among law enforcement officers, complexities in digital evidence, and tensions between protecting individual reputation and safeguarding freedom of expression. These obstacles indicate that legal enforcement has not yet functioned optimally. Strengthening the capacity of law enforcement authorities, improving clarity in legal interpretation, and enhancing public legal awareness are essential to ensure balanced, fair, and effective enforcement of defamation law in cyberspace.